Prilog unapređenju autobusnoga linijskog tranzitnog prometa - Štefančić, Gordana (Promet - Traffic&Transportation, 2012)
This paper deals with the specific aspects of liner bus traffic reviewed based upon the information provided by the Main Zagreb Bus Station. A couple of recommendations have been given for the aspired-to improvement of transit passenger transport transit bus traffic and international transit traffic by methods of transport projections of volumes and flows.